KARAKTERISTIK FISIK DAN KIMIA AIR DADIH (WHEY) DANGKE DENGAN LEVEL ENZIM PAPAIN YANG BERBEDA (Chemical and Physical Properties of Dangke Whey Using Different Levels of Papain Enzyme) - Sulmiyati Sulmiyati (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2017)
Dangke is a typical food from South Sulawesi, especially in Enrekang made from casein milk with a clotting enzyme papain from papaya. The study was conducted to determine the propertys of whey the waste products dangke and designed in accordance with the completely randomized design 3 treatments provision papain enzyme solution 10-2 at concentration of 0.5%; 1%; and 1.5% with 5 replications. Parameters measured pH, production of curd, whey percentage, percentage of lactic acid, lactose content, protein content. The results showed that the addition of papain enzyme solution did a signifcant effect (P <0.05) on physical propertys of whey and no signifcant effect (P> 0.05) on the chemical propertys of whey. The best results with the use of papain enzyme solution 10-2 at concentration of 1%.